2022
DOI: 10.1126/scitranslmed.abf3685
|View full text |Cite
|
Sign up to set email alerts
|

A bivalent Epstein-Barr virus vaccine induces neutralizing antibodies that block infection and confer immunity in humanized mice

Abstract: Epstein-Barr virus (EBV) is the major cause of infectious mononucleosis and is associated with several human cancers and, more recently, multiple sclerosis. Despite its prevalence and health impact, there are currently no vaccines or treatments. Four viral glycoproteins (gp), gp350 and gH/gL/gp42, mediate entry into the major sites of viral replication, B cells, and epithelial cells. Here, we designed a nanoparticle vaccine displaying these proteins and showed that it elicits potent neutralizing antibodies tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(41 citation statements)
references
References 51 publications
0
30
0
Order By: Relevance
“…The epitopes of 3A3 and 3A5 defined in this study represent the major immunogenic sites specific for EBV gB in human sera. This study highlights the importance of the neutralizing antigenic sites at gB D-II and D-IV together with those at gp350 and gHgL recognized by neutralizing antibodies ( 18 , 24 , 32 , 35 ) for the rational design of successful anti-EBV vaccines and therapeutics.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…The epitopes of 3A3 and 3A5 defined in this study represent the major immunogenic sites specific for EBV gB in human sera. This study highlights the importance of the neutralizing antigenic sites at gB D-II and D-IV together with those at gp350 and gHgL recognized by neutralizing antibodies ( 18 , 24 , 32 , 35 ) for the rational design of successful anti-EBV vaccines and therapeutics.…”
Section: Discussionmentioning
confidence: 84%
“…Given that EBV elicits broad antibody responses against its glycoproteins in humans, the gB epitopes recognized by 3A3 and 3A5 could be exploited in combination with the other antigenic sites on gp350 and gHgL recognized by the neutralizing mAbs 72A1, AMMO1, 769B10, and 1D8 ( 18 , 24 , 32 ) for the design of potent vaccines. The recent exciting studies reported the design of nanoparticles displaying gp350 and/or gHgL, which elicited potent neutralizing antibodies against EBV infection ( 32 , 35 ). Carefully designed approaches that combine multiple EBV immunogens and properly expose these neutralizing antigenic sites could be further explored to induce broader and stronger immunity against EBV infection.…”
Section: Discussionmentioning
confidence: 99%
“…However, since the vaccines are based on human HLA, functional evaluation is actually difficult to be carried out using routine experimental animals. Even though there are humanized mice, it is still recognized that testing the vaccine in such a model would be difficult ( 104 , 105 ). Nonetheless, it is possible to determine in vitro if the antibodies generated were neutralizing and to determine the cytolytic potential of the T cells ( 106 , 107 ).…”
Section: Discussionmentioning
confidence: 99%
“…Long-term persistence of cellular and humoral immunity may provide more robust protection against EBV-associated diseases. It is also important to emphasize that while vaccine formulations based on EBV glycoproteins (gp350, gH/gL and gH/gL/gp42) have shown some protection against EBV infection in humanized mice 51 , it is unlikely that the antibodies directed to these glycoproteins alone can offer protection against latent EBV infection. In contrast, previous studies have clearly demonstrated that adoptive immunotherapy with latent antigenspeci c T cells can reverse the outgrowth of EBV malignancies and offer clinical bene t to patients with progressive MS 41,52−54 .…”
Section: Discussionmentioning
confidence: 99%